Gooseberry Microbiota during Storage - Natalya V. Motovilova; Olga V. Golub; Galina P. Chekryga (Техника и технология пищевых производств)
Berries are a source of biologically active substances in human diet. Gooseberries have attractive sensory properties and high nutritional value. However, modern science knows little about micromycetic contamination of gooseberry. The research objective was to define the mycobiota composition of Ribes uva-crispa L. varieties during storage. The study featured the mycobiota of gooseberry varieties Senator and Rozoviy 2. The berries were harvested on the test field of the Siberian Federal Scientific Center of Agro-BioTechnologies of the Russian Academy of Sciences. They were stored for 18 days at 18 ± 2 and 4 ± 2°C and a relative humidity of 90–95%. The authors used standard research methods to identify the mycobiota and attribute them to nine genera by morphological structure: Aspergillus, Mucor, Penicillium, Rhizopus, Alternaria, Aureobasidium, Cladosporium, Cryptococcus, and anaerobic yeast. The frequency of occurrence varied from 20 to 100%. Micromycetes of the genus Fusarium were present only in the Senator sample, which also demonstrated a 100% occurrence of Penicillium, Alternaria, Aspergillus, and Cladosporium. In the sample of Rozoviy 2, Penicillium and Cladosporium occurred in 80%. The Senator sample was twice as low in micromycetes as the Rozoviy 2 berries: 558 vs. 945, respectively. The Senator berries grew in micromycetes due to the Cladosporium fungi while Rozoviy 2 owed its micromycetic increase to Penicillium. Both varieties showed no signs of ascomycetes known as a powdery mildew agent. During storage, the growth of yeast and yeast-like fungi depended on the variety of berries while the growth of mycelial fungi depended on the variety and storage temperature. The data obtained expand the scope of scientific knowledge about the generic composition of gooseberry mycobiota, which may help to select correct anti-spoilage measures.